Unlocking the potential of microalgae-derived therapeutic carriers: Characteristics, types, and nanomedical applications - Peiyi Wang; Changhong Liu; Lei Zheng (Materials Today Bio, 2025)
Traditional drug delivery systems are constrained by limitations such as low drug-loading efficiency, immunogenicity, and functional simplicity, rendering them inadequate to address the demands of complex pathological scenarios. Microalgae have emerged as a promising alternative system, possessing not only health benefits derived from their bioactive compounds but also inherent properties that naturally align with delivery system requirements. These advantageous characteristics include exceptional biocompatibility, easily modifiable surface properties, and photosynthetic oxygen-generating capacity. Therefore, using microalgae to develop functional natural delivery systems that combine the delivery of therapeutic substances with the regulation of body health is promising. This review provides a detailed exposition of microalgae-based delivery strategies, including the characteristics, advantages, and types of both microalgae and their derived delivery systems. Furthermore, it pays particular attention to their delivery applications in various biomedical fields, as well as the clinical progress, research gaps, and future trends. Overall, microalgae have great potential for the development of natural delivery systems that promote organismal health and enhance biological functionality. In the future, the integration of emerging biosensing and nanotechnologies with microalgae platforms holds great promise for advancing next-generation therapeutic delivery systems with intelligent responsiveness, precise targeting, and personalized treatment capabilities.